2018
DOI: 10.5812/iji.60181
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Acinetobacter baumannii Isolated from Patients with Urinary Tract Infections in Zabol, Iran

Abstract: Background: Acinetobacter baumannii are opportunistic pathogens that are found in abundance in Zabol. Due to their unique capability for long-term survival in the hospital environment, the chances of becoming infected with the bacteria are very high. Therefore, identifying potential sources of infection in the donor is very important. The aim of this study was to determine antibiotic resistance in Acinetobacter isolates. Methods: A cross sectional study was performed to evaluate 30 strains of Acinetobacter bau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
1
Order By: Relevance
“…Despite most reports and in agreement with the results of studies by Rahimi and Rezaie Keikhaie et al, Acinetobacter spp. isolates showed partly good sensitivity to gentamicin (40%) (37,38). In contrast to the results of the current study, Mortazavi et al (39) reported very high resistance to gentamicin and amikacin simultaneously among 80 A. baumannii strains from Ahvaz, south-west Iran.…”
Section: Discussioncontrasting
confidence: 90%
“…Despite most reports and in agreement with the results of studies by Rahimi and Rezaie Keikhaie et al, Acinetobacter spp. isolates showed partly good sensitivity to gentamicin (40%) (37,38). In contrast to the results of the current study, Mortazavi et al (39) reported very high resistance to gentamicin and amikacin simultaneously among 80 A. baumannii strains from Ahvaz, south-west Iran.…”
Section: Discussioncontrasting
confidence: 90%
“…Another study showed that the MIC of gentamicin was 1024 µg/mL (20). In a study by Rigi and Sancholi, who investigated the antimicrobial activity of Solanum nigrum, the results showed that the MICs of the methanolic extract of leaf were 12.5, 25, and 25 ppm against bacteria Aeromonas hydrophila, Yersinia racria, and Streptococcus inuia, respectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…, SMILES-based, graph-based, and hybrid descriptors (a combination of SMILES and graph) for the creation of QSAR models. 30,31…”
Section: Methodsmentioning
confidence: 99%